Study of Implementation of Safety Standards in Tehran University of Medical Sciences Hospitals General Stores - R Sharifian; F Faraji Khiavi; SMH Mousavi; G Shaham (Tehran University of Medical Sciences, 2009)
Background and Aim: General Store department is responsible for on time preparing commodities for hospitals departments. It's a place for saving materials and resources. Safety in store department and its materials has importance due to preserving high quality and continuous services.General Store department safety should be audited by assessment System to reduce waste materials and human resources such as building, commodities and patient and personnelُ s lives; and in case of facing with a problem, try to solve it. The aim of this study was determination of safety standards in hospital general stores in TUMS.Materials and Methods: This research was conducted as a cross-sectional study safety and usage of management principles was advised and measured in hospitals of TUMS; sampling was nُ t performed. Results: Safety rate in research population was more than 85/42 percent. Score in safety aspects like as physical spaces, preventing robbery, blazing materials appropriate storing, commodities arrangement, utilizing suitable tools was more than 80%. Protection against fire and storing rote able materials estimated 79% and 77%. Safety rate in several aspects was assessed in the study hospitals.Discussion and Conclusion: Although, hospital store rooms assessed as safe; but they should try to develop fire protection systems and store rote able materials preservation appropriately.